EFL Students’ Integrative and Instrumental Motivation in Learning English (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2021)
Motivation impacts the rate and success of foreign language learning. It compensates for deficiencies in language proficiency and learning. This research focuses on describing the students’ motivation in learning English viewed from integrative and instrumental motivations. The data about the students’ motivations were collected using a closed-ended questionnaire given online via a google form. In order to get broader data, the writer took the samples of this study from two English Departments of two universities, STKIP PGRI Sidoarjo and UNP Kediri. In the integrative aspect, the results showed that eighty-seven percent respondents’ motivation to learn English was because English is an important language in the world. Then, seventy percent of respondents stated that they are also motivated to learn English because they want to be able to explore the English-speaking regions, communicate with native speakers and be able to use English with English-speaking friends. However, fifty-seven respondents stated that learning English culture, history and literature were less important. In the instrumental aspect, eighty percent respondents motivated to learn English because English can help them to get a better future career. Then sixty-eight respondents answered that they wanted to fulfil the foreign language requirement and they make themselves to be a more qualified job candidate. Their educational purposes also drove them to learn English. While their desire to fulfil their study candidates or be able to speak more languages were less important. It suggested to English teacher to focus on promoting learning experiences that considers students’ motivations.